TEACHING STRATEGIES USED BY ENGLISH TEACHERS IN ONLINE LEARNING - Cahyaningsih, Putu Devi; Putra, I Nyoman Adi Jaya; Mahendrayana, Gede (International Journal of Language and Literature, 2021)
This study aimed at finding out teaching strategies used by English teachers in an online learning. The subject of this study is English teachers at SMP Negeri 6 Singaraja. This study was qualitative research which uses a case study research design. The methods of data collection were observation and interview. This study used three instruments such as observation checklist, questionnaire, and interview guide. The findings showed that English teachers at SMP Negeri 6 Singaraja used learning by doing and learning by reflection in the online learning. Four English teachers were considering about aspects of learning by doing and learning by reflection. Besides, during the online learning, it was found five obstacles. The English teachers were also provided the solutions for the obstacles.